Acute Onset Isolated Sixth Nerve Palsy Secondary to a Metastatic Brain Lesion. - Crowell, Benjamin D.; Sears, Joan M.; Joy, Jeffrey T. (Journal of Behavioral Optometry, 2012)
Introduction: A sixth nerve palsy causes binocular horizontal diplopia due to a paretic lateral rectus muscle, particularly in the direction of the involved muscle. Over the age of 50, vasculopathic (diabetes and hypertension) etiology is most common. Monitoring until resolution is typically the course of treatment. Further testing may be required, when indicated by systemic findings. Case Report: A 55-year-old male presented with recent onset diplopia and restricted ocular motility left eye in left gaze. He denied headache, pain, or recent injury. There were no signs or symptoms of transient ischemic attacks/ stroke, flashes, floaters, vision loss, or any other ocular symptoms. Further questioning found no jaw claudication, recent weight loss, temporal pain, or other associated signs of giant cell arteritis. Medical history revealed hypertension and prostate cancer. An MRI of the brain confirmed an enhancing clival mass adjacent to Meckle's cave consistent with metastatic disease. An immediate referral to oncology was made. The patient's PET scan revealed multiple metastatic lesions throughout his body. The patient is currently being treated with extensive chemotherapy and radiation. Visually, the patient continues to improve subjectively through use of a head turn and patching as needed. Objectively, the patient's deviation remained relatively stable through four months before being lost to follow-up. In this case, the patient showed subjective improvement due to learned behaviors and patching but little, if any, objective improvement was seen. Discussion: The two most common etiologies for sixth nerve palsy are vasculopathic and unknown, followed more rarely by traumatic and metastatic events. This patient presented with a brain neoplasm involving the left petrous apex and clivus. It is at this bony extension where the sixth nerve runs most medially and compression forces can result in nerve palsy. Although a metastatic etiology of sixth nerve palsy is less common, a patient presenting with such a history warrants earlier additional testing. INSET: 1.